ANALISA PENERAPAN DIGITALISASI SISTEM PEMBAYARAN PBB TERHADAP EFEKTIVITAS PENERIMAAN PBB DI KELURAHAN SUKABUMI UTARA - Dina Era Ermawati; Aliffia Rosada Nibros; Sintia Intan Nuraini; Nadia Lusiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of digitalization in the Land and Building Tax (PBB) payment system and its effectiveness on PBB revenue realization in Sukabumi Utara Subdistrict. The research is motivated by the government’s need to improve efficiency, transparency, and accuracy in tax payment processes through the use of digital technology. A descriptive qualitative method was employed, with data collected through interviews, observations, focus group discussions (FGD), and analysis of PBB revenue documents from 2017 to 2024. The findings reveal that digitalization through mobile banking, e-commerce platforms, and payment points has technically simplified the payment process. However, its effectiveness has not reached its full potential due to gaps between the ideal digital system and actual conditions in the field. Key obstacles include low levels of digital literacy among residents, limited socialization regarding regulatory changes, annual variations in PBB policies, and difficulties accessing or downloading digital Tax Notification Letters (SPPT). The revenue data also show significant fluctuations, which are more strongly influenced by fiscal policy changes than by digitalization itself. This is evident from sharp increases in revenue in 2020 and 2023, driven by adjustments in property value assessments (NJOP) and tax exemption policies. Gap analysis indicates that fiscal regulations exert a stronger influence than the convenience offered by digital payment systems. The study concludes that while digitalization enhances efficiency and transparency, improved tax revenue requires more intensive regulatory socialization, automated notification systems, and stable policy frameworks. Recommendations include providing digital assistance services at the subdistrict office and improving community digital literacy to optimize PBB revenue and local government income.